IMPLEMENTASI PEMBELAJARAN KITAB WAṢAYĀ AL-ABĀ’ LIL-ABNĀ’ DALAM PEMBENTUKAN AKHLĀK AL-KARĪMAH SANTRI DI PONDOK PESANTREN AN-NAHDLAH SUDIANG KOTA MAKASSAR - Rosmini; Idah Suaidah; Erwin Hafid; Syahruddin; Besse Ruhaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This thesis aims to describe the planning of learning the book Waṣayā al-Abā’ lil-Abnā’ at An-Nahdlah Islamic Boarding School, Sudiang, Makassar City; to describe the implementation of learning the book Waṣayā al-Abā’ lil-Abnā’ in shaping the moral character of students (santri); to describe the evaluation process of learning the book in fostering students’ akhlāk al-karīmah (noble character); and to identify the supporting and inhibiting factors in the learning process.This study employed a descriptive qualitative research design. The data collection techniques used were observation, interviews, and documentation. The findings reveal that the learning plan was systematically designed by preparing the book as the primary learning resource and determining instructional methods that were adjusted to the students’ levels of ability. The implementation of learning was carried out systematically, beginning with classroom management, the application of various teaching methods, and concluding activities that included reinforcement of the material by the teacher. The evaluation process was conducted through written, oral, and practical assessments. In fostering akhlāk al-karīmah at An-Nahdlah Islamic Boarding School, several supporting factors were identified, including teachers’ competence, the use of varied instructional methods, and the students’ motivation and enthusiasm. Meanwhile, the inhibiting factors included limited instructional time, low proficiency in Arabic language skills, and inadequate educational facilities and infrastructure.